A Experience of Emeregncy Nurses in Performing Cardiopulmonary Resucitation (CPR) in Denpasar, Bali - Ni Luh Seri Astuti; Ida Ayu Wiwin Apsari Wahyuni; I Dewa Ayu Nyoman Manik Ulandewi; Triyana Puspa Dewi; Ni Made Sintha Pratiwi (Babali Emergency and Disaster Research, 2023)
Introduction: When the heart stops beating, blood flow throughout the body stops, which is known as cardiac arrest. Cardiopulmonary resuscitation (CPR) is necessary as quickly as feasible in cardiac arrest. When meeting cardiac arrest patients, nurses typically feel uneasy and anxious because they feel unqualified and untrained to do cardiopulmonary resuscitation.The purpose of this study is to thoroughly examine nurses' experiences with cardiopulmonary resuscitation in cardiac arrest patients in the ER Dharma Yadnya Hospital. Methods: a single case study qualitative research design utilizing thematic analysis methods. Snowball sampling is the sample method, and there are 6 participants. In-depth interviews were used to acquire the data. Results: (1) Cardiopulmonary resuscitation management, (2) Nurse's emotional description when performing CPR, (3) Supporting factors for the success of CPR, (4) Unstable family emotions, patient's physical condition and poor coordination of the medical team, (5) Nurses' calmness as seen from professionalism, (6) Practice taking action in panic situations and (7) psychological readiness prior to performing CPR. Conclusion: Despite having the skills to do CPR, ED nurses were anxious about performing it. They later experienced psychological harm as well. Education that encourages CPR skills and support networks to lessen psychological discomfort for ED nurses could be beneficial.